Thymoma in a 14 Month Female with Mild Pure Red Cell Aplasia - Tiwari, S; Bafna, V; Shrotriya, S; Kalrao, V; Lalwani, S (Journal of Nepal Paediatric Society, 2015)
Thymoma is a rare case presenting in the paediatric age group. Only 30 cases have been reported so far. Our case is a 14 month old female, presented with respiratory distress. CT scan showed gross widening of superior mediastinum with a homogeneous opacity. Immunohistochemistry was suggestive of thymoma. She underwent excision of the thymic mass and is well at present. J Nepal Paediatr Soc 2015;35(1):76-78